Impacts of technology assisted science teaching on students learning outcome for 9th grade students in a private school in Dubai - NEMER, REEMA (2019)
The search for learning and teaching methods has led to the exploration of various methods such as traditional and technology integrated. In addition to that, there has been controversies surrounding the use of technology in the classroom. This study is conducted to determine the effectiveness of integrating technology methods over the traditional teacher-centered way of teaching science classes. The aim of the study is test how effective integration of ICT is in the classroom. Key studies consulted in this study are the numerous literature synthesis that have been done by previous researchers on the use of technology in class rooms. In this study, a mixed method research design is applied, involving experimental design and the use of questionnaires. The experiential approach was used to make comparisons between the two methods, while surveys helped determine the attitudes of teacher, students and their parents towards the use of technology-assisted teaching methods in the class. Both the experiential and control groups with 15 students and had similar scores in the pre-test exams. They were then taught two science lessons with the same teacher, but using different methodologies. The test group learned using technology-assisted methods while the control group learned through the traditional methods. Both students and parents took part in the experiment that lasted for 12 weeks. After data analysis, the findings showed that integrating technology in the classroom is more effective than the traditional teacher-centered method for 9th-grade science classes in terms of academic achievement.